Histories of host shifts and cospeciation among free‐living parasitoids of Rhagoletis flies. (27th July 2016) - Hamerlinck, G.; Hulbert, D.; Hood, G. R.; Smith, J. J.; Forbes, A. A.
Abstract: Host shifts by specialist insects can lead to reproductive isolation between insect populations that use different hosts, promoting diversification. When both a phytophagous insect and its ancestrally associated parasitoid shift to the same novel host plant, they may cospeciate. However, because adult parasitoids are free living, they can also colonize novel host insects and diversify independent of their ancestral host insect. Although shifts of parasitoids to new insect hosts have been documented in ecological time, the long‐term importance of such shifts to parasitoid diversity has not been evaluated. We used a genus of flies with a history of speciation via host shifting ( Rhagoletis [Diptera: Tephritidae]) and three associated hymenopteran parasitoid genera ( Diachasma, Coptera and Utetes ) to examine cophylogenetic relationships between parasitoids and their host insects. We inferred phylogenies of Rhagoletis, Diachasma, Coptera and Utetes and used distance‐based cophylogenetic methods (ParaFit and PACo) to assess congruence between fly and parasitoid trees. We used an event‐based method with a free‐living parasitoid cost model to reconstruct cophylogenetic histories of each parasitoid genus and Rhagoletis . We found that the current species diversity and host–parasitoid associations between the Rhagoletis flies and parasitoids are the primary result of ancient cospeciation events. Parasitoid shifts to ancestrally unrelated hosts primarily occur near the branch tips, suggesting that host shifts contribute to recent parasitoid species diversity but that these lineages may not persist over longer time periods. Our analyses also stress the importance of biologically informed cost models when investigating the coevolutionary histories of hosts and free‐living parasitoids.